Atrazine Persistence in Sediment of Aquatic Microcosms - Torres, Luana Dandara Barreto; Coelho, Lucia Helena Gomes (Environmental Protection Research, 2023)
Atrazine is a mutagenic, carcinogenic, and environmentally persistent herbicide commonly detected in natural waters and sediment due to its broad use in corn, sugarcane, and sorghum plantations. Though largely studied, investigations on atrazine’s fate and routes of transformation in freshwater environments have been somewhat scarce and fragmented. Thereby, the purpose of this study is to comprehend the physicochemical destiny of atrazine in the sediment of laboratory-based aquatic freshwater microcosms. Four microcosms with a capacity of 40 L were set up in the laboratory after the preparation of standard synthetic sediment (composed of peat moss, medium-sized grain sand, and white clay) and filled with tap water. Two of these systems (labeled 1 and 3) were contaminated with atrazine, resulting in an overall initial concentration of 100 μg L-1 in each, whereas the other two systems (labeled 2 and 4) were maintained under control conditions. The assays were monitored for 43 weeks in total, for pH, dissolved oxygen (DO), total dissolved solids (TDS), apparent color, turbidity, and temperature. Atrazine was added to the systems only in the 14th week (100 μg L-1) and quantified in the water column in the 38th week (46 μg L-1) through liquid chromatography coupled to mass spectrometry, showing that the initial concentration of atrazine in the water column decayed by approximately 50% during this period. This finding indicates that the herbicide underwent biological and/or physicochemical transformations in the water column and sediment. The systems’ water was replaced in the 40th week, after which the atrazine concentration in the water column returned to equilibrium (46 μg L-1), revealing that the sediment can function as a repository of the compound in the systems’ aquatic environment.